2014
DOI: 10.1016/j.fob.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer drug mithramycin interacts with core histones: An additional mode of action of the DNA groove binder

Abstract: HighlightsMithramycin (MTR) binds to core histones but not to linker histone H1.Unlike MTR–DNA interaction, MTR–histone association is metal independent.MTR alters H3K18 acetylation in vitro and ex vivo.MTR is a dual binder (binds to both DNA and histones) in the chromatin context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…A solution (DNA‐EB) containing DNA (100 μ m ) and EB (10 μ m ) was made in buffer, 5 m m Tris–HCl/50 m m NaCl (pH = 7.2). The fluorescence emission spectra were recorded at λ ex 490 nm for solutions of varying concentrations (5, 10, 15, 20, 25, 30, 35 and 40 μ m ) of compounds ( S ) ‐L 1 H , ( S ) ‐L 2 H , ( S ) ‐1 and ( S ) ‐2 in the presence of DNA‐EB after incubation of these solutions at RT for 10 min 48a–d . The emission spectra obtained in the absence and presence of increasing amounts of the above compounds are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution (DNA‐EB) containing DNA (100 μ m ) and EB (10 μ m ) was made in buffer, 5 m m Tris–HCl/50 m m NaCl (pH = 7.2). The fluorescence emission spectra were recorded at λ ex 490 nm for solutions of varying concentrations (5, 10, 15, 20, 25, 30, 35 and 40 μ m ) of compounds ( S ) ‐L 1 H , ( S ) ‐L 2 H , ( S ) ‐1 and ( S ) ‐2 in the presence of DNA‐EB after incubation of these solutions at RT for 10 min 48a–d . The emission spectra obtained in the absence and presence of increasing amounts of the above compounds are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…However, the fluorescence emission spectra of these compounds showed that there was no appreciable change of emission intensity of DNA‐EB with increasing concentrations, indicating a non‐intercalative mode of interaction with CT‐DNA 15f . The fluorescence quenching capability of these compounds was evaluated from Stern–Volmer constant, K sv , which was determined using the following equation: 48 IO/I=1+Ksv[]M where I O and I correspond to the fluorescence intensities in the absence and presence of compounds respectively, [ M ] is the concentration of compounds (quenching agent, Q) and K sv is the linear Stern‐Volmer constant. A graph for I O / I against [ M ] for each of these compounds is shown in the inset of Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown SP1-independent gene expression after MitA treatment [ 46 , 47 ]. By examining OA-associated genes and signaling pathways, we identified HIF-2α as a factor specifically down-regulated by MitA.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that MitA can regulate histone modifications, resulting in dysregulation of NF-κB activation. Besides DNA, MitA can also bind to core histones present in chromatin and inhibit histone H3 acetylation to regulate gene expressions [ 47 ]. Moreover, MitA can inhibit a subset of class I histone deacetylase expression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that combined SP1 knockdown/p53 over-expression did not fully recapitulate growth inhibition and gene expression profiles observed in MM-treated MPM cells suggests that additional as yet uncharacterized mechanisms contribute to MM-mediated cell cycle arrest, senescence and apoptosis in MPM cells. For example, recently described interactions of MM with core histones could account, in part, for repression of genes lacking prototypic SP1 or p53 recognition elements within their respective promoters {Banerjee, 2014 3218 /id}. Experiments are underway to examine these issues, and to ascertain if small molecule mdm2-p53 inhibitors {Zhang, 2015 3222 /id} or agents which inhibit p21 expression {Nguyen, 2004 1774 /id} can augment MM-mediated apoptosis in MPM cells.…”
Section: Discussionmentioning
confidence: 99%